Language assessment : - Brown, H. Douglas (Longman, 2003)
Language Assessment provides teachers with a clear presentation of the essentials for assessing second language learning fairly and effectively. This updated second edition includes new research and information on standardized tests, a new chapter on form-focused assessment, and a concise glossary of terms. With a focus on the most common pedagogical challenge — classroom-based assessment — Language Assessment delivers useful tools for evaluating and designing practical, effective assessment techniques.